PENTINGNYA PERANCANGAN IDENTITAS VISUAL BAGI KOMUNITAS KEWIRAUSAHAAN SMPN 2 TRAWAS KABUPATEN MOJOKERTO: THE IMPORTANCE OF DESIGNING A VISUAL IDENTITY FOR THE ENTREPRENEURIAL COMMUNITY OF SMPN 2 TRAWAS MOJOKERTO REGENCY - Laylur Rohman; Aileena Solicitor Costa Rica El Chidtian (Pakis Journal Institute, 2023)
Visual identity is a crucial element in the modern business world full of intense competition. Creating a strong visual identity that distinguishes itself is an inevitable strategic step in facing competitors. Unfortunately, SMPN 2 Trawas, which has an active entrepreneurial community, does not yet have a visual identity that reflects the character and spirit of the community. Therefore, the main objective of this activity is to build an education and training program that can utilize visual identity as an effective tool to improve the skills and knowledge of the entrepreneurial community members. This activity took place over three days. In this way, the new visual identity not only creates visual appeal, but also becomes the foundation for strengthening and advancing the SMPN 2 Trawas entrepreneurship community as a whole. The results of this activity show that students can create a visual identity for the entrepreneurship community.